2022
DOI: 10.3390/agriculture12122001
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Opportunities to Collect Semen and Sperm Cells for Ex Situ In Vitro Gene Conservation in Sheep

Abstract: The semen of domestic mammals is conventionally collected with an artificial vagina (AV) for artificial insemination (AI) or for short- or long-term storage. However, the procedure has certain drawbacks: animal training is not feasible in extensive animal care systems nor among wild species, as the trained animals sometimes fail to mount. Hence, there is a need for alternative semen collection methods. Electroejaculation (EEJ) and epididymal sperm recovery (ESR) are the two effective alternatives to AV. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Sheep are associated with several endogenous and exogenous factors that can vary significantly between individuals and breeds, affecting the effectiveness of AI [ 5 , 6 ]. The impact of exogenous factors, such as estrus induction, synchronization [ 7 , 8 ], semen collection methods [ 9 ], and choices between fresh, chilled, or frozen semen [ 10 ], has been the subject of extensive studies in the context of ovine AI. However, it is equally important to recognize the impact of endogenous factors to the success of ovine AI programs.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep are associated with several endogenous and exogenous factors that can vary significantly between individuals and breeds, affecting the effectiveness of AI [ 5 , 6 ]. The impact of exogenous factors, such as estrus induction, synchronization [ 7 , 8 ], semen collection methods [ 9 ], and choices between fresh, chilled, or frozen semen [ 10 ], has been the subject of extensive studies in the context of ovine AI. However, it is equally important to recognize the impact of endogenous factors to the success of ovine AI programs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they can be used to preserve the genetic resources of elite rams. Our literature review, published recently, has revealed that collection of the epididymal spermatozoa is an ideal alternative for gene conservation because it has a recovery rate comparable to the use spermatozoa obtained by the use of artificial vagina (AV) and serves as the easiest and cheapest means of conserving livestock GnR (Mujitaba et al, 2022). Considering the limited published articles on factors affecting the quality of ram epididymal spermatozoa (REPS), we hypothesised that ram breed and collection methods might significantly affect the motility and kinematic parameters of the fresh sample and cryotolerance of REPS.…”
Section: Introductionmentioning
confidence: 99%